Strategi Penggunaan Training dan Daily Worker pada Masa Pandemi Covid-19 Serta Dampak terhadap Peningkatan Kinerja di The Kanjeng Hospitality Management Bali - Apriani, Hilda; Satiaji, Amirosa Ria; Murdana, I Ketut (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2022)
The Covid 19 pandemic that has occurred from 2020 until now has greatly affected every business. The world of Bali tourism is very impacted by the occurrence of this pandemic. The hotel business sector that is still operating carries out strategies that can save and make business operations run well. Kanjeng Hospitality Management, as a company engaged in the hospitality sector, has implemented an efficiency strategy by using training and daily workers to support the company's operations during the pandemic. This study was conducted to analyze the strategy using the SWOT method (strengths, weaknesses, opportunities, threats). The results of data collection show that the strategy of using training and daily workers is effective in saving the salary budget up to 50% of the normal budget. Training and daily workers also have good productivity because they are able to complete work well. Although it does not have a significant impact in improving the performance of permanent employees, this strategy is an aggressive strategy, because it has great strengths and opportunities so that it can be maximized to bring about increased business operations.